The Future of Food: Scenarios for 2050 - Hubert, Bernard; Rosegrant, Mark W.; Boekel, Martinus A.J.S. van; Ortíz, Rodomiro (Wiley, 2010)
This background article addresses key challenges of adequately feeding a population of 9 billion by 2050, while preserving the agro‐ecosystems from which other services are also expected. One of the scenario‐buildings uses the Agrimonde platform, which considers the following steps: choosing the scenarios and their underlying building principles, developing quantitative scenarios, and building complete scenarios by combining quantitative scenarios with qualitative hypotheses. These scenarios consider how food issues link to production, for example, the percentage of animal vs. vegetal calorie intake in the full diet. The first section of this article discusses Agrimonde GO and Agrimonde 1 scenarios, which indicate that global economic growth and ecological intensification remain as main challenges for feeding the earth's growing population toward the mid‐21st century. The second section provides the outcomes of the analysis of alternative futures for agricultural supply and demand and food security to 2050, based on research done for the International Assessment of Agricultural Science and Technology for Development. The last section of this article provides a summary analysis of food systems and functions, as well as the role of food technology that address some of the global challenges affecting the supply of more nutritious and healthy diets. It also highlights the food production by novel means (e.g., alternatives for animal products based on plant materials) and increasing the presence of potentially health‐promoting compounds in food to improve human and animal health. Finally, this article proposes priority areas that should be included in further agri‐food research.